MODAL POLITIK PASANGAN H.MAHMUD ABDULLAH DAN DEWI NOVIANY PADA PEMILIHAN UMUM KEPALA DAERAH KABUPATEN SUMBAWA TAHUN 2020 - DEDI SUPRIADI; IRAWANSYAH IRAWANSYAH (Universitas Mahasaraswati K. Mataram, 2023)
The couples of H.Mahmud Abdullah and Dewi Noviany who are often called as MONOVI are carrying the motto as Sumbawa Gemilang, this couple are the winning pairs in the Sumbawa Regency general election 2020. This research focuses on looking in depth at what political capital the MONOVI pair are using in getting the most votes in the 2020 Sumbawa Regency. Meanwhile, the method presented in this study is a qualitative method with a case study model and data collection techniques using three stages, namely observation, in-depth interviews and documentation or literature research related to the problems presented. As for the data analysis technique using the Miles interactive method, the data analysis in this study consisted of three streams of activities that occurred simultaneously, namely: data condensation, data presentation and conclusion/verification. The data found is tested for validity by analyzing and clarifying it with an implementation model. The results of the study show that this couple uses three political capitals including: political capital, then social capital and finally economic capital. Of the three political capitals, the pair of H. Mahmud Abdullah and Dewi Noviany are more dominant in using political capital and social capital than economic capital then economic capital.